Holistic care, implementation of physical activity and a healthy lifestyle in patients with PMS symptoms - Lepczyński, Bartłomiej; Kułakowska, Aleksandra; Siedlak, Agnieszka; Kłakowicz, Philip; Lechowski, Sebastian (Journal of Education, Health and Sport, 2023)
Effective control of fertility and new social roles of women caused that the time when a woman experiences cyclical hormonal changes in the menstrual cycle and the possible adverse symptoms associated with it became the period prevailing during the reproductive period of a woman’s life. Premenstrual syndrome (PMS) comprises clinically significant physical and psychological symptoms that occur during the luteal phase of the menstrual cycle and cause significant distress and functional impairment. A broadly understood change in lifestyle, diet, systematic increase in physical activity, reduction of stimulants, but above all, keeping a diary of observation of alarming symptoms positively affects the improvement of women’s well-being, accelerates the diagnosis and start of treatment.